DEVELOPMENT OF A CHEMO-ENTREPRENEURSHIP BASED CHEMISTRY PRACTICUM E-MODULE USING THE PROJECT BASED LEARNING MODEL ON COLLIGATIVE PROPERTIES OF SOLUTIONS - Dewi Uchsin Nadiya; Hilya Ulinnaja (UIN Mataram, 2026)
Chemistry learning emphasizes not only conceptual understanding but also laboratory activities to help students comprehend concepts in a concrete and contextual manner. However, learning materials at SMAN 1 Patianrowo are still dominated by printed textbooks, while limited laboratory equipment and materials have led to infrequent implementation of chemistry practicum activities. Consequently, students' engagement in learning, particularly on the topic of colligative properties of solutions, remains low. This study aimed to develop a chemo-entrepreneurship-based chemistry practicum e-module using the Project-Based Learning model on the topic of colligative properties of solutions. The product is an e-module published through the Heyzine Flipbook platform, integrating the chemo-entrepreneurship approach with the Project-Based Learning syntax through projects involving the production of ice cream, fruit syrup, gummy candy, and candied fruit. The e-module also includes Break-Even Point (BEP) calculations, Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis, as well as interactive QR codes providing access to demonstration videos, supplementary learning materials, practice exercises, and learning evaluations. This study employed the Research and Development (R&D) method using the 3D development model (Define, Design, and Develop). The research sample consisted of 36 twelfth-grade students in Class XII-1. The results indicated that the developed e-module was categorized as highly valid based on material expert validation (83.28%) and media expert validation (83.12%), highly practical according to students' responses (85.48%), and moderately effective in improving learning outcomes, with an N-Gain score of 56%. ABSTRAK Pembelajaran kimia tidak hanya menekankan pemahaman konsep, tetapi juga memerlukan kegiatan praktikum agar peserta didik dapat memahami materi secara konkret dan kontekstual. Namun, bahan ajar di SMAN 1 Patianrowo masih didominasi oleh buku paket, dan keterbatasan alat serta bahan praktikum menyebabkan kegiatan praktikum kimia jarang dilaksanakan, sehingga keterlibatan peserta didik dalam pembelajaran, khususnya pada materi sifat koligatif larutan, masih rendah. Penelitian ini bertujuan untuk mengembangkan e-modul praktikum kimia berbasis chemo-entrepreneurship dengan model project-based learning pada materi sifat koligatif larutan. Produk berupa e-modul yang dipublikasikan melalui platform Heyzine Flipbook mengintegrasikan pendekatan chemo-entrepreneurship dengan sintaks project-based learning melalui proyek pembuatan es krim, sirup buah, permen gummy, dan manisan buah. E-modul juga memuat analisis Break-Even Point (BEP), Strengths, Weaknesses, Opportunities, Threats (SWOT), serta QR Barcode interaktif untuk mengakses video demonstrasi, materi pendukung, latihan soal, dan evaluasi pembelajaran. Penelitian ini menggunakan metode Research and Development dengan model pengembangan 3D (define, design, develop). Sampel penelitian terdiri atas 36 peserta didik kelas XII-1. Hasil penelitian menunjukkan bahwa e-modul memperoleh kategori sangat valid dari ahli materi (83,28%) dan ahli media (83,12%), sangat praktis berdasarkan respons peserta didik (85,48%), serta cukup efektif dalam meningkatkan hasil belajar dengan persentase N-Gain sebesar 56%.